Escherichia coli Isolated from Urinary Tract Infections of Lebanese Patients between 2000 and 2009: Epidemiology and Profiles of Resistance. (12th October 2011) - Daoud, Ziad; Afif, Claude
Abstract : The purpose of this study was to investigate the bacterial etiology of urinary tract infections in one of the busiest hospitals of Lebanon and to examine the epidemiologic and microbiologic properties of Escherichia coli isolated from urinary tract infections of Lebanese patients over a 10-year period. Methods . This retrospective study analyzed the data generated between 2000 and 2009 (10, 013 Gram-positive and Gram-negative bacteria). Bacterial identification was based on standard culture and biochemical characteristics of isolates. Antimicrobial susceptibility was tested by the disk diffusion method, and ESBL production was detected by synergy with third-generation cephalosporins and amoxiclav. Results . E. coli was the most frequent isolate throughout the ten years (60.64% of the total isolates). It was followed by Klebsiella pneumoniae and Proteus sp., Pseudomonas aeruginosa, Enterococcus sp., and Streptococcus agalactiae . E. coli occurred more frequently in women (69.8%) than in men (61.4%). The lowest percentage of susceptibility of E. coli was manifested against piperacillin and ampicillin. An increase in the production of ESBL was observed (2.3% in 2000 to 16.8% in 2009). Conclusions . The etiology of urinary tract infections and their susceptibility profiles are important to be evaluated in countries like Lebanon where a severe misuse of antibiotics at all levels is observed.